Socialization of Introduction to Sharia Economics at the Alamul Huda Islamic Boarding School - Suci Rahmawati; Emy Nailis; Saila Arzaqina; Ismatul Khaliyah; Hendri Hermawan Adinugraha; Aris Syafi’I (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
This service is carried out with the background of wanting to contribute in increasing the level of understanding to provide knowledge to the santri community. The purpose of this community service is to increase knowledge about Islamic economics, especially regarding Islamic banking. It is hoped that the results of this training will provide additional new understanding from the surrounding community. This activity was carried out using the method of presentation, discussion, and observation. The presentation method is used in the process of delivering training materials. The expected output targets from this activity are 1) The community is able to know and understand the sharia economic system; 2) The public gains a new understanding of what Islamic banking is and how it differs from conventional banking; 3) Furthermore, the community will be able to know and understand how to obtain funds in developing a better and blessed life.